Attunement as the Core of Therapist-Expressed Empathy - Macaulay, Helen L.; Toukmanian, Shaké G.; Gordon, Kimberley M. (Canadian Journal of Counselling and Psychotherapy, 2008)
The communication of empathic understanding was examined in relation to three qualities of therapist interventions (attunement, tentativeness, and meaning exploration) and tested for its relationship to client in-session processing. High and low client-process segments, from sessions of 20 mild-moderately depressed clients treated in brief experiential therapy, were rated for therapist empathy and manner of responding. Client responses were evaluated for depth of experiencing and manner of perceptual processing. Empathy was significantly greater in high than in low client-process segments. Analyses revealed that together the three qualities of therapist interventions predicted level of empathy, butattunement emerged as the sole significant individual predictor.